Partial-Thickness Bursal-Site Rotator Cuff Repair With Autologous Bursa Augmentation - Marco T. Di Stefano, M.D.; Michael Young, B.S.; Jonas Vorbau, B.S.; Alexa Cohen; Stefan Minyayluk, B.S.; Alireza Gholipour, Ph.D.; Mary Beth McCarthy, B.S.; Augustus D. Mazzocca, M.D., M.S. (Arthroscopy Techniques)
Rotator cuff tears are persistent problems that motivate clinicians to explore innovative solutions to enhance patient healing outcomes. Bursal cells have proliferative, differentiating, and migrating properties, making them a feasible solution to this problem. This article aims to show a possible solution for symptomatic, refractory bursal-sided rotator cuff tears using a bio-inductive scaffold (BIS) with bursa augmentation. This procedure is eligible for patients with bursal-sided rotator cuff tears that have been refractory to conservative treatment. The surgical technique consists of an augmentation of a BIS filled with minced bursal tissue, a source of mesenchymal stem cells (MSCs). The scaffold serves as a barrier to hold the bursal cells on top of the lesion, promoting cell-to-cell contact between tenocytes and MSC-rich bursal cells, thereby enhancing their full potential. This surgical technique is a straightforward, reproducible, and effective approach to enhancing rotator cuff repair. By using autologous bursal MSCs and a BIS, this technique promotes healing, potentially reducing retear rates and accelerating recovery. The use of the BIS further supports the repair, ensuring optimal tissue healing in the tendon-bone junction.